PETANI DALAM PERSPEKTIF ANTROPOLOGI EKONOMI - Akhmad Zaini Abar (Agro Ekonomi, 2002)
The concepts of rational and moral choices are both of ideal types in social science. These are only use for a social analysis and not for a social engineering. The rational peasants do not indicate the rational choice that have been introduced by Samuel L. Popkin, they are, on the other hand, in moral choice that have been stated by James C. Scott. The commercialization of peasants and agricultural sectors do not reflect the rational peasant's movement. In the essay, the Indonesian case, the commercialization of peasants are an effect of the state's project of colonial era and the New Order, these aren't the articulation of the rational peasants.